PEMBATALAN PERKAWINAN AKIBAT PERKAWINAN LEBIH DARI SATU ISTRI TANPA IZIN MENURUT HUKUM POSITIF - Rinawati Kadarrisman; Sifa Mulya Nurani (Kampus Akademik Publiser, 2026)
Under Indonesian positive law, polygamy is permitted only if it meets the requirements stipulated by legislation, including obtaining permission from the Religious Court and the consent of the first wife. The practice of unauthorized polygamy involving the manipulation of administrative data can result in the annulment of the marriage. This study aims to analyze the legal regulations regarding unauthorized polygamy, the judicial considerations in Ruling Number 3245/Pdt.G/2025/PA.Bks, and the legal consequences of marriage annulment. The research employs a normative-juridical method utilizing both statutory and case-based approaches. Legal materials were gathered through a literature review and analyzed using a descriptive-qualitative method. The findings indicate that unauthorized polygamy contravenes Law Number 1 of 1974 concerning Marriage (as amended by Law Number 16 of 2019), Government Regulation Number 9 of 1975, and the Compilation of Islamic Law. Ruling Number 3245/Pdt.G/2025/PA.Bks provides legal certainty and protection for the aggrieved party through the mechanism of marriage annulment.